2022
DOI: 10.1136/jitc-2021-003978
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigens as potential vaccines in hepatocellular carcinoma

Abstract: BackgroundNeoantigens, new immunogenic sequences arising from tumor mutations, have been associated with response to immunotherapy and are considered potential targets for vaccination. Hepatocellular carcinoma (HCC) is a moderately mutated tumor, where the neoantigen repertoire has not been investigated. Our aim was to analyze whether tumors in HCC patients contain immunogenic neoantigens suitable for future use in therapeutic vaccination.MethodsWhole-exome sequencing and RNAseq were performed in a cohort of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Nevertheless, we have demonstrated that some neoAgs identified in murine vaccination experiments were immunogenic in vitro using human cells from healthy donors. We have recently reported equivalent results for immunogenicity of neoAgs identified in hepatocellular carcinoma patients ( 41 ), demonstrating not only the activity of HLA class I-restricted neoAgs but also for class II binding peptides. Thus, our current results obtained in TNBC patients suggest that the TMB found may originate a sufficient number of neoAgs for vaccination.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, we have demonstrated that some neoAgs identified in murine vaccination experiments were immunogenic in vitro using human cells from healthy donors. We have recently reported equivalent results for immunogenicity of neoAgs identified in hepatocellular carcinoma patients ( 41 ), demonstrating not only the activity of HLA class I-restricted neoAgs but also for class II binding peptides. Thus, our current results obtained in TNBC patients suggest that the TMB found may originate a sufficient number of neoAgs for vaccination.…”
Section: Discussionmentioning
confidence: 86%
“…Underlying neoantigens produced by nsSNVs in HCC were identified by WES and RNA sequencing. Most predictive peptides bound to HLA-A*02.01 and HLA-DRB1*01 representative class I and class II alleles and enjoyed immunogenicity, providing a novel strategy for HCC treatment 28 . It was noteworthy that nsSNVs and neoantigen loads were associated with checkpoint inhibitor responses.…”
Section: The Origin Of Neoantigenmentioning
confidence: 99%
“…HCC is a moderately mutated tumor. Recently, Repáraz et al compared the results of whole-exome sequencing and RNAseq analyses performed on malignant and normal tissues obtained from fourteen HCC patients [ 107 ]. A median of 1217 missense somatic single nucleotide variants were identified per patient in malignant tissues; of these, a median of 13 and 5 peptide sequences (neoantigens) per patient were predicted to bind HLA class I and class II molecules, respectively.…”
Section: Clinical and Preclinical Applicationsmentioning
confidence: 99%